Phenotyping Rice Germplasm Associated With Salinity Tolerance Under Hydroponics System (Bangladesh Agronomy Journal, 2022)
Screening of different rice (Oryza sativa L.) germplasms or breeding lines is a continuous effort to identify the promising source. A series of experiments (20) were undertaken to identify promising materials for five years of salinity screening from 2015 to 2019. The materials included total of 3,195 rice germplasm and breeding lines, out of which Bangladesh Rice Research Institute (BRRI) developped 2, 295 germplasms, 193 advanced breeding lines from BRRI, and 707 advanced breeding lines from International Rice Research Institute (IRRI), Philippines. From this study, the genotypes were categorized as 122 tolerant, 220 moderately tolerant, 1,207 sensetive, and 1,646 highly sensetive. Among the BRRI germplasms, most of the materials (61%) had sensitive responses against salinity, while only 2 and 3% of rice germplasm exhibited tolerant and moderately tolerant, respectively. BRRI lines comprised 44% sensetive and 35% highly sensetive rice genotypes. In the tolerance level, 4% appeared as tolerant and 17% moderately tolerant against salinity. Likewise, IRRI lines also showed relatively higher tolerance (9%) than the BRRI germplasm and lines. They were classified into 9 % tolerant and 16 % moderately tolerant rice genotypes.Bangladesh Agron. J. 2022, 25(1): 37-45